Piety Aspects in the Holy Qur’an - Haddad, Marwan Mohammad (Journal of Islamic Sciences, 2022)
This research aims mainly to reveal the relationship between piety and its aspects and its practical connections based on what is cited in the verse: “O Prophet, we have sent you as a witness, a herald and a warner”1. It was found that the Holy Qur’an, through the verse, has identified three goals for the message of Prophet Muhammad (PBUH) which are: faith and belief in the existence and oneness of Allah (SWT), as well as belief in his angels, books and messengers (witnessing), guidance to implement and achieve what is stated in the Qur’an, clarification and explanation of what is permissible and what is not permissible (a bearer of good tidings), and a warning of the consequences and the reckoning of recompense for the deeds committed (a warner). In the introduction, piety and its meanings, definitions, and formulas were presented and clarified, in addition to the importance of piety in Islam. It came in two sections: In the first, the aspects of piety in the Holy Qur’an were analyzed, including the classification of piety in three interrelated and mutual aspects: faith, application and accounting piety. In the second, five important relationships of piety in Islam were presented and detailed including: the relationship between faith and piety, sincerity, interdependence, exchange and integration in aspects of piety, the ways to achieve piety, and the relationship between intention and piety. The method used in the research is a combination of the descriptive and inductive method and the content analysis method. The research was completed with a conclusion section that included the most important achieved results.